Analyzing the Performance of the Population Health Environment on the Promotion of Provincial Governors in China - Hsiao, Hsiao-Fen; Zhao, Meng-Han; Liao, Wen-Ju (Frontiers in Public Health, 2021)
China's economy has achieved rapid growth, but the change has also brought about serious environmental degradation, which is the main factor endangering human health. This study empirically investigates the impact of the population health environmental index on the promotion of provincial governors using an ordered probit model. The sample of the study consists of regions where provincial governors, municipal mayors, and autonomous region chairmen were stationed from 1995 to 2015. The results show that the population health environmental index had a significant and positive impact on governors' promotions, especially in the eastern region. The reformation of the population health environmental index assessment system for government officials was the initial factor that brought about these effects.